A review of privacy and usability issues in mobile health systems: Role of external factors. (September 2019) - Katusiime, Jane; Pinkwart, Niels
The increased penetration of mobile devices has created opportunities in the health sector and led to emerging of mobile health systems. As much as the mobile health systems have registered tremendous progress, they have been faced with privacy and usability issues. Due to the sensitivity of health information, there is an ethical need to equip mobile health systems with adequate privacy measures. However, these systems should also be useable by the intended users. Even though many researchers are working on solutions, the issues still persist. External factors such as cultural differences have also contributed to the issues, yet they have been under researched. In this article, we conduct a systematic literature review of 22 articles, categorize and present privacy and usability issues and possible solutions. We then discuss the relevance and implications of external factors to the findings on privacy and usability. We end with recommendations to address these external factors.